Improved accuracy optimal tuning method for hydropower units' governor controller. Issue 1 (May 2020) - Niasse, Mouhamed; Zheng, Qi; Xin, Ai; Quan, Federico Flamenco; Saleem, Adeel; Iqbal, Atif
Abstract: This paper aims to improve the model of the hydro-turbine system under the effect of water-hammer for frequency-domain studies. It brings out a novel way to overcome the accuracy limitation linked to the simple first and second-order approximations of the gate-turbine transfer function. The proposed study is based on the detailed model of the hydraulic system considering the effects of water compressibility and pipe elasticity. The improved system is controlled using particle-swarm optimization algorithm, which is shown to be very efficient in controlling the overshoot and stability of the system connected to a single machine single load test system. Step response and load disturbance are simulated. Results from our example prove that covering accurately a frequency range from 0 to over 30Hz is easily made when using this method for frequency-domain simulations of hydropower plant load-frequency control.